Liberia : Poverty Reduction Strategy; Progress Report. (IMF Staff Country Reports; Country Report ;, 2010)
Liberia made slow progress on the implementation of the Poverty Reduction Strategy (PRS). The impact of the global economic crisis affected implementation and slowed the pace of growth. With the development of the Public Financial Management (PFM) framework, a PRS deliverable, the credibility of the country's financial systems is being restored. Increased vigilance in tax collection efforts, expansion of the tax base, and the elimination of discretionary exceptions led to a rise in revenue by 13.5 percent from USD 207 million in fiscal year (FY) 2007/08 to USD 235 million in FY2008/09.